KEBIJAKAN INDONESIA DALAM MELARANG EKSPOR MINERAL MENTAH TAHUN 2009-2014 (Studi Kasus: Larangan Ekspor Mineral Mentah Nikel ke Tiongkok) - Gust Satriawan; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research will explain why Indonesia banned the export of raw minerals out of State that is described in the study case of a ban on the export of nickel mineral to Tiongkok. The purpose of this research is to find out how the mining mineral in Indonesia, and how the necessity of Tiongkok about nickel mineral in Indonesia and to discover why Indonesia banned the export of nickel mineral to Tiongkok that is listed in the regulations No.4 of 2009. Indonesia is reputed to be the world's largest exporter of minerals but why Indonesia banned the export of nickel minerals to abroad in the middle of the conditions under which each country sought to increase his country's export value respectively.The method that used is library research where the data were obtained from sources that are relevant to the research problems are discussed. This research uses the perspective of mercantilism, and theories of foreign policy as well as the concept of national interest according to Jack C.Plano and Roy Olton.The results of this research indicate that the purpose of Indonesia stop the export of raw nickel minerals to Tiongkok is to increase the export value of nickel minerals that will be exported. Through the regulations No.4 of 2009, Indonesia aims to improve mine activities by attempting to build a smelter or tools to process the raw nickels in order to increases the sell value of nickel aboard. Construction of the smelter in Indonesia is expected to increase revenue through exports of nickel from Indonesia to abroad. Keywords: Mining, nickel, Smelters, Regulations No.4 of 2009.